Impact of the ocean-atmosphere coupling on high-resolution future projections for the Mediterranean sea and surrounding climate from the Med-CORDEX ensemble - Soto-Navarro, Francisco Javier; Jordà-Sánchez, Gabriel; Somot, Samuel; Sevault, Florence (My University, 2022)
Med-CORDEX is an international initiative that aims at developing fully coupled high resolution Regional Climate System Models (RCSMs) for the Mediterranean basin. After 11 years of work an ensemble of more than 25 multi-model and multi–scenario climatic simulations is now available (Darmaraki et al., 2019; Soto-Navarro et al., 2020). In this study, we analyze the impact of the high-resolution representation of the Mediterranean Sea and of the interaction between ocean and atmosphere, explicitly resolved in the Med-CORDEX simulations, in the projected evolution of the most relevant climatic variables for the Mediterranean basin and the adjacent regions during the 21st century. The final goal is to quantify up to what extent including the explicit and high-resolution representation of the ocean-atmosphere coupling is relevant for regional climate projections. The preliminary results show that, in general, higher resolution coupled simulations project a lower increase in the Sea Surface Temperature (SST) than lower resolution runs. This translates in a smaller input of heat and humidity to the atmosphere that, in turn, affect the cloud cover and precipitation over the basin and the adjacent continental areas. These changes are the result of a better representation of the Mediterranean Sea functioning in the Med-CORDEX RCSMs. In particular, they resolve better the mesoscale processes of the basin, which are partly responsible of the heat transport from the surface to deeper layers, and the ocean-atmosphere feedback that regulates the heat exchange.
Keywords: Clima - Cambios - Congresos; Mediterráneo (Región) - Congresos; Circulación oceánica - Modelos matemáticos - Congresos; Mediterranean Sea; Climate Change; Ocean Modelling